2015
DOI: 10.1038/ncomms8002
|View full text |Cite
|
Sign up to set email alerts
|

The molecular landscape of colorectal cancer cell lines unveils clinically actionable kinase targets

Abstract: The development of molecularly targeted anticancer agents relies on large panels of tumourspecific preclinical models closely recapitulating the molecular heterogeneity observed in patients. Here we describe the mutational and gene expression analyses of 151 colorectal cancer (CRC) cell lines. We find that the whole spectrum of CRC molecular and transcriptional subtypes, previously defined in patients, is represented in this cell line compendium. Transcriptional outlier analysis identifies RAS/BRAF wild-type c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
309
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 263 publications
(338 citation statements)
references
References 46 publications
(62 reference statements)
28
309
1
Order By: Relevance
“…Several studies show that CRC cell lines recapitulate the main molecular phenotypes observed in primary CRC (Ahmed et al ., 2013; Barretina et al ., 2012; Berg et al ., 2017; Medico et al ., 2015; Mouradov et al ., 2014), which substantiate their value as preclinical model systems to assess a variety of pharmacogenomic relationships. Consistent with the observed clinical benefit in patients with CDX2‐negative tumors in stage III, loss of CDX2 expression was strongly associated with sensitivity to conventional chemotherapeutics in vitro , both in our drug screen dataset and in a large public dataset, again independent of MSI status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that CRC cell lines recapitulate the main molecular phenotypes observed in primary CRC (Ahmed et al ., 2013; Barretina et al ., 2012; Berg et al ., 2017; Medico et al ., 2015; Mouradov et al ., 2014), which substantiate their value as preclinical model systems to assess a variety of pharmacogenomic relationships. Consistent with the observed clinical benefit in patients with CDX2‐negative tumors in stage III, loss of CDX2 expression was strongly associated with sensitivity to conventional chemotherapeutics in vitro , both in our drug screen dataset and in a large public dataset, again independent of MSI status.…”
Section: Discussionmentioning
confidence: 99%
“…Although the frequency of ALK fusions in colorectal carcinoma is low, the incidence of 0.2% translates into approximately 265 patients in the United States each year and approximately 2,800 patients worldwide each year. The relatively broad range of ALK fusion frequencies in colorectal cancer varying from 0.13% to 2.5% described in previous studies (Supplementary Table S1) may be related to different patient cohorts analyzed, in some studies limited to 40 cases, and different testing methodologies, including IHC, FISH, real-time PCR, exon array, comprehensive genomic profiling, and transcriptome analysis (6,7,(11)(12)(13)(14)(15). In contrast, in this study, ALK rearrangements were identified in a cohort of 3,157 patients with colorectal carcinoma using CGP and cohort of 2,980 patients with colorectal carcinoma by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the epithelial cancers they are most common in non-small cell lung cancer (NSCLC), comprising approximately 3% to 7% of lung adenocarcinoma (10), while only nine cases of colorectal carcinoma harboring ALK fusions have been described in seven previous studies (refs. 6,7,(11)(12)(13)(14)(15)Supplementary Table 1). Tumors with ALK rearrangements express activated fusion kinases composed of the intact ALK tyrosine kinase domain fused with different unrelated gene partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously reported that colorectal cancer cell models harboring NTRK1 translocations are sensitive to NTRK1 silencing and to TRKA (protein encoded by the NTRK1 gene) kinase inhibition (5)(6)(7). Based on this, the patient was enrolled in the phase I ALKA clinical trial (EudraCT Number 2012-000148-88) of the pan-TRK kinase inhibitor entrectinib, a fi rst-in-class drug currently undergoing clinical testing ( 3 ).…”
Section: Acquired Resistance To Trka Inhibition In a Patient With Colmentioning
confidence: 99%